Charge transfer excitons in unfunctionalized graphite-wrapped MAPbBr3 nanocrystal composites with different morphologies. (14th April 2022) - Nim, Gaurav Kumar; Ghosh, Sukanya; Saini, Saurabh Kumar; Kumar, Mahesh; Kar, Prasenjit
Abstract : Charge transfer from perovskite nanocrystals to graphite sheets. Abstract : Highly luminescent methylammonium lead halide perovskite nanocrystals (PNCs) have attracted considerable research interest due to their alluring properties that can be tuned as per the morphological variations. Charge transfer excitons (CTEs) are a good representation of the capacity of semiconductor materials to tune their properties. We report here that CTEs may be generated successfully in graphite:PNC composites functioning as host–guest components. These hybrid perovskite nanocrystals are embedded in graphite sheets that are unfunctionalized. The PL spectrum demonstrated that graphite significantly reduces the luminescence intensity of the perovskite nanocrystals. The morphologies of the perovskite nanocrystals are developed in such a manner that they may be readily incorporated onto the surface of graphite sheets to facilitate effective charge transfer.